2015
DOI: 10.4238/2015.october.16.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bcl-2-siRNA on proliferation and apoptosis of pediatric acute B lymphoblastic leukemia (A-BLL) cells

Abstract: ABSTRACT. This study analyzed the effect of small interfering RNA specific for the Bcl-2 gene (siRNA Bcl-2) on the proliferation and chemotherapeutic sensitivity of pediatric A-BLL cells. Marrow samples were obtained from sixty newly-diagnosed A-BLL pediatric patients. The Bcl-2 mRNA expression in these samples was quantified by real time polymerase chain reaction. The Bcl-2 mRNA re-expression was analyzed by RNA interference using Bcl-2-siRNA. Cellular proliferation was detected using the MTT (Thiazolyl Blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(24 reference statements)
0
2
0
1
Order By: Relevance
“…The findings of the present study are consistent with previous research on leukemia. The therapeutic method of this study using siRNA could significantly downregulate Mcl-1 mRNA in Ju- On the other hand, another study by Meng et al on pediatric patients with A-BLL demonstrated that transfection of Bcl-2-siRNA into leukemic cells significantly increased the apoptosis rate (36).…”
Section: Discussionmentioning
confidence: 59%
“…The findings of the present study are consistent with previous research on leukemia. The therapeutic method of this study using siRNA could significantly downregulate Mcl-1 mRNA in Ju- On the other hand, another study by Meng et al on pediatric patients with A-BLL demonstrated that transfection of Bcl-2-siRNA into leukemic cells significantly increased the apoptosis rate (36).…”
Section: Discussionmentioning
confidence: 59%
“…Recent evidence also shows that selective targeting of these pathways has cytotoxic effects on cancer stem cells (See Table 2). (Bolomsky et al, 2020) Bcl family proteins/gene silencing (i) Bcl-2 siRNA and antisense nucleotides (Gagliardi and Ashizawa, 2022;Meng et al, 2015) (ii) Bim-1 siRNA (Schwulst et al, 2008;Wakabayashi et al, 2021) Targeting p53…”
Section: Drugs Targeting Autophagymentioning
confidence: 99%
“…Meng et al 21 indicated that the paediatric ALL patients in the drug-resistance group showed significantly higher Bcl-2 mRNA expression, compared to those in the chemotherapy sensitive group. In addition, the Bcl-2 mRNA expression in chemo-sensitive patients decreased significantly after chemotherapy, while the expression of Bcl-2 mRNA in the drug-resistant group did not alter significantly before and after chemotherapy.…”
mentioning
confidence: 99%